Heat treatment method for improving performance of beta titanium alloy joint, obtained beta titanium alloy joint and application

By adopting a two-stage aging heat treatment method of first low temperature and then high temperature on β titanium alloy joints, the problem of increased grain size and reduced tensile strength in the weld area after welding is solved, the strength and hardness of the joints are increased, and the welding process is improved. Mechanical properties of structural parts.

CN119351917APending Publication Date: 2025-01-24CHINA-UKRAINE INST OF WELDING GUANGDONG ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411582194.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

After β-titanium alloy welding, the grain size of the weld area increases, the in-crystal dislocation density decreases, resulting in a decrease in tensile strength. The welding structural parts are prone to mismatch in mechanical properties and priority breakage at the welded seams during service. .

Method used

The β-titanium alloy joint is heat treated using a two-stage aging method of first low temperature and then high temperature. Through low-temperature aging, the nano-ω phase is transformed into an ellipsoid shape, and the nano-α phase is precipitated next to the ω phase. These nano-phases are then eliminated at high temperature to achieve Uniform and fine distribution of α precipitated phase in β phase matrix.

Benefits of technology

Effectively improve the strength and hardness of the β -titanium alloy connector, improve the mechanical properties of the welding structure component, and avoid priority breaks at the weld.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119351917A_ABST
    Figure CN119351917A_ABST
Patent Text Reader

Abstract

The invention discloses a heat treatment method for improving the performance of a beta titanium alloy connector, the obtained beta titanium alloy connector and application. According to the technology / heat treatment method for improving the mechanical performance of the beta titanium alloy connector through intermediate nanophase transformation, through a low-temperature and high-temperature multi-step aging mode, harmful nanophase is eliminated, and meanwhile the mechanical performance of the beta titanium alloy connector is improved. And uniform and refined distribution of an alpha precipitated phase in a beta phase matrix is realized, so that the strength and hardness of the beta titanium alloy joint are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of welding processing, and in particular to a heat treatment method for improving the performance of a beta titanium alloy joint, the obtained beta titanium alloy joint and applications. Background Art

[0002] β-type titanium alloy has the characteristics of high specific strength, light weight, corrosion resistance, fatigue resistance, and good high and low temperature performance. It is an ideal choice for lightweight equipment structure and ensuring service reliability. In addition, this type of titanium alloy has better room temperature strength, fracture toughness and hardenability than α+β alloys, and can be used in the manufacture of large structural parts. Welding is a common process for manufacturing large equipment, and the quality of welds is crucial to the reliability of welded structures. β-alloys have excellent welding properties. In previous studies, researchers used laser welding, electron beam welding and other methods to prepare β-alloy welded joints.

[0003] However, after welding, the weld area of ​​the β-titanium alloy undergoes a quasi-solid solution process from high-temperature melting to rapid cooling. The microstructure of the β-titanium alloy weld area is therefore transformed into coarse β-columnar crystals. The increase in grain size leads to a decrease in dislocation density within the crystal, which is not conducive to resisting deformation. The tensile strength is therefore reduced, and the welded structural parts will experience mechanical property mismatch and preferential fracture at the weld during service. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and to provide a heat treatment method for improving the performance of a β-titanium alloy joint, the obtained β-titanium alloy joint and its application.

[0005] The present invention solves the technical problem by adopting the following technical solutions.

[0006] The invention provides a heat treatment method for improving the performance of a beta titanium alloy joint, which comprises: heat treating the beta titanium alloy joint in a double-stage aging mode of first low temperature and then high temperature.

[0007] The present invention also provides a high-strength and high-hardness β-titanium alloy joint prepared according to the above heat treatment method.

[0008] The present invention also provides an application of the heat treatment method in the treatment of the weld seam of a β-titanium alloy post-weld joint.

[0009] The present invention has the following beneficial effects:

[0010] The present invention provides a heat treatment method for improving the performance of a β-titanium alloy joint, the obtained β-titanium alloy joint and its application. The present invention takes a β-titanium alloy joint as the object, and through a low temperature + high temperature multi-step aging method, while eliminating harmful nanophases, realizes uniform and refined distribution of α precipitated phase in the β phase matrix, thereby effectively improving the strength and hardness of the β-titanium alloy joint. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0012] Figure 1 The SEM image of the metallographic structure of the weld area in the embodiment;

[0013] Figure 2 This is a TEM dark field image of the weld area of ​​the joint of the embodiment;

[0014] Figure 3 This is a TEM dark field image of the joint weld area after the primary aging treatment of the embodiment;

[0015] Figure 4 This is a SEM image of the metallographic structure of the weld zone of the joint after secondary aging treatment in the embodiment. DETAILED DESCRIPTION

[0016] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0017] The following is a detailed description of a heat treatment method for improving the performance of a β-titanium alloy joint, the obtained β-titanium alloy joint and its application provided in an embodiment of the present invention.

[0018] In a first aspect, an embodiment of the present invention provides a heat treatment method for improving the performance of a β titanium alloy joint, which comprises: heat treating the β titanium alloy joint by a two-stage aging method of first low temperature and then high temperature.

[0019] During the welding process of β-titanium alloy joints, the weld zone undergoes a process of cooling and solidifying from an extremely high temperature molten state in a short time, which has a similar thermal process to high temperature rapid quenching. This will cause the precipitation of ω phase in the weld zone of β-titanium alloy. This type of nano-ω phase has the highest elastic modulus and hardness and is a harmful hard and brittle phase in titanium alloys. Therefore, post-weld heat treatment is a common means to improve the mechanical properties of joints, and plays a decisive role in the microstructure and mechanical properties of joints.

[0020] However, the heat treatment system of β-titanium alloy joints needs to be specially designed, and conventional titanium alloy heat treatment methods are not applicable. First, as mentioned above, there is a hard and brittle nano-ω phase in the β-titanium alloy joint, which needs to be eliminated to improve the mechanical properties of the joint. Second, β-titanium alloy is also prone to precipitate nanophases during the low-temperature aging process, such as the transformation of part of the ω phase into the α phase. Although these nanophases can improve the strength of the material, they will also seriously reduce the plasticity of the material. Third, as mentioned above, there are still coarse β columnar crystals in the β-titanium alloy joints. Although the traditional aging heat treatment can promote the nucleation and growth of the α phase in the weld zone, which helps to improve the tensile strength of the joint, the precipitation of the α phase occurs preferentially on the grain boundaries and intergranular defects, and the uneven phase distribution leads to limited effect of improving the strength of the joint.

[0021] In order to overcome the shortcomings mentioned in the above-mentioned prior art, the present invention takes β-titanium alloy joints as the object, and provides a heat treatment method for improving the mechanical properties of β-titanium alloy joints by using intermediate nanophase transformation. Through a two-stage aging treatment method of first low temperature and then high temperature, the low temperature can transform the dispersed nano ω phase in the β-titanium alloy joint into an ellipsoidal shape, and a fine needle-shaped nano α phase is precipitated next to the ω phase. After aging treatment at a higher temperature, the ellipsoidal ω phase and the nano needle-shaped α phase can disappear, and at the same time, the uniform and refined distribution of the α precipitate phase in the β phase matrix is ​​achieved. The above two-stage aging treatment can not only eliminate harmful nanophases, but also evenly distribute a large number of fine α precipitates in the β phase matrix, thereby effectively improving the mechanical properties of the β-titanium alloy joint.

[0022] In some optional implementations, the two-stage aging method is: firstly, primary aging is performed at an aging temperature below the α phase transition temperature, and then secondary aging is performed at an aging temperature above the α phase transition temperature.

[0023] An embodiment of the present invention provides a heat treatment method for improving the performance of β-titanium alloy joints, firstly performing primary aging at an aging temperature below the α phase transformation temperature, and then performing secondary aging at an aging temperature above the α phase transformation temperature. By controlling the temperature of the double-stage aging, the nano-ω phase existing in the weld zone of the joint can be transformed into an ellipsoidal shape through the primary aging treatment under low temperature conditions, and a fine needle-shaped nano-α phase is precipitated next to the ω phase, rather than precipitating the nano-α phase at the grain boundary and intergranular defects. Then, a secondary aging treatment is performed under high temperature conditions to make the ellipsoidal ω phase and the nano-needle-shaped α phase disappear, and transform into a lath-shaped α phase structure evenly distributed in the β matrix. Thereby effectively improving the strength and hardness of the β-titanium alloy joint.

[0024] In some optional embodiments, the β-titanium alloy joint is prepared by the following steps: two titanium alloy plates are connected by fusion welding or additive manufacturing, and then naturally cooled to room temperature by air cooling, wherein the thickness of the titanium alloy plate is 1-100 mm.

[0025] In some optional implementations, the weld center structure of the β titanium alloy joint is: a large number of coarse β columnar crystals + dispersed fine nano ω phases.

[0026] In some optional embodiments, the temperature of the primary aging treatment is 200-400° C., the heating rate is 5-10° C. / min, and the holding time is ≥5h.

[0027] In some optional implementations, the central structure of the β-titanium alloy joint weld after primary aging treatment is: ellipsoidal ω phase + nano-needle-shaped α phase next to the ellipsoidal ω phase.

[0028] In some optional embodiments, the temperature of the secondary aging treatment is 500-700° C., the heating rate is 1-5° C. / min, and the holding time is 5-10 h.

[0029] In some optional embodiments, the central structure of the weld in the β titanium alloy joint after secondary aging treatment is: lath-like α phase.

[0030] In some optional embodiments, the steps include:

[0031] Preparation of welding joint: two titanium alloy plates are connected by fusion welding or additive manufacturing, and then naturally cooled to room temperature by air cooling, wherein the thickness of the titanium alloy plate is 1-100 mm;

[0032] Primary aging treatment: Place the joint in a heat treatment furnace, heat it up to 200-400℃ at a heating rate of 5-10℃ / min, and keep it warm for ≥5h;

[0033] Secondary aging treatment: the temperature in the heat treatment furnace is raised at a heating rate of 1-5°C / min and stabilized at 500-700°C, and the holding time is 5-10h;

[0034] Air cooling: After the insulation is completed, the β-titanium alloy joint is directly taken out for air cooling.

[0035] As can be seen from the above, the embodiment of the present invention provides a heat treatment method for improving the performance of β titanium alloy joints, which includes: adopting low temperature + high temperature double-stage aging, and controlling the temperature control method of the double-stage aging treatment temperature, time and heating rate, while eliminating harmful ω phase, achieving the uniform and refined distribution of beneficial α phase in the β phase matrix. Wherein: when the primary aging temperature is lower than 200°C, there is not enough driving force to transform the athermal ω phase to the isothermal ω phase, and the athermal ω phase cannot intervene in the refinement behavior of α by assisting the precipitation of α phase like the isothermal ω phase, that is, the solution provided by the embodiment of the present invention, first by transforming the uniformly distributed athermal ω phase into a uniformly distributed isothermal ω phase, under the assistance of the isothermal ω phase, the α phase is uniformly precipitated; when the temperature is higher than 400°C, the (α+β) phase region has been reached at this time, so the α phase is directly precipitated from the β matrix at this time, and the dissolution of the isothermal ω phase no longer affects the size of the α precipitated phase. In the above two cases, the mechanical properties of the secondary aging and the single-step aging are not much different. In terms of holding time, the longer the holding time, the more isothermal ω phases are obtained, and the stronger the refinement effect on the α precipitation phase of the secondary aging. Therefore, under the effect of dispersion strengthening, the β titanium alloy joint has higher strength and hardness. In the secondary aging, too low an aging temperature will lead to insufficient driving force for the precipitation of the α phase, and the strengthening effect of the two-phase alloy cannot be achieved. When the aging temperature is higher than 700°C, part of the α phase will dissolve in the β matrix, resulting in a decrease in the strengthening effect. In terms of holding time, as the holding time increases, the α phase will coarsen, causing the β titanium alloy joint to soften, the strength and hardness to decrease, and the ductility to increase.

[0036] In a second aspect, an embodiment of the present invention further provides a high-strength and high-hardness β-titanium alloy joint prepared according to the above-mentioned heat treatment method.

[0037] In a third aspect, an embodiment of the present invention further provides an application of the above-mentioned heat treatment method in the treatment of weld seams of post-weld joints of β-titanium alloy.

[0038] The present invention will be further described below in conjunction with the embodiments.

[0039] A heat treatment method for improving the performance of a β titanium alloy joint, wherein the titanium alloy plate is Ti-35421, comprises the following steps:

[0040] a. Preparation of welding joints: Melt welding is performed on the β titanium alloy, and then naturally cooled by air cooling after welding. The thickness of the titanium alloy plate is 1-100mm. The welding methods include electron beam welding, laser welding, plasma welding, and arc welding. Figure 1 This is the SEM image of the metallographic structure of the weld area, showing that there are a large number of coarse β columnar crystals in the center of the weld. Figure 2 This is the TEM dark field image of the joint weld area, where dispersed fine nano-ω phase (white dots) can be observed.

[0041] b. First step aging: Place the joint in a heat treatment furnace and heat it to 200-400℃ at a heating rate of 5-10℃ / min. The first step aging holding time is ≥5h. Figure 3 As shown in the TEM dark field image, after the first step of aging treatment, the dispersed nano-ω phase in the β-titanium alloy joint is transformed into an ellipsoidal shape, and small needle-shaped nano-α phase is precipitated next to the ω phase.

[0042] c. Second step aging: In the same furnace, heat up to 500-700℃ at a heating rate of 1-5℃ / min and keep warm. The second step aging insulation time is 5-10h.

[0043] d. After the insulation is completed, take out the joint directly for air cooling. Figure 4 The SEM image of the metallographic structure of the weld area after heat treatment shows that Figure 1 In contrast, a large number of fine-sized α precipitates appeared inside the β grains.

[0044] The specific heat treatment process parameters in the embodiments and comparative examples are shown in Table 1 below.

[0045] Table 1 Heat treatment process

[0046]

[0047]

[0048] The mechanical properties of the prepared titanium alloy joints were tested with reference to GB / T 2651-2023 "Destructive test of welds of metallic materials - Transverse tensile test" and GB / T4340.1-2024 "Vickers hardness test of metallic materials". The test results are shown in Table 2 below.

[0049] Table 2 Test results

[0050]

[0051]

[0052] Combining the above Tables 1 and 2, it can be seen that the mechanical properties of the weld area of ​​the prepared β-titanium alloy joint can be significantly improved by adopting the solution provided by the embodiment of the present invention. Specifically, in terms of the microhardness of the weld area, the average microhardness of the β-titanium alloy joint prepared in Example 1 is as high as 482.7HV, while the average microhardness of the β-titanium alloy joint prepared in Comparative Example 1 is 298.0HV, showing the significant effect of multi-step aging treatment. In other comparative examples, such as Comparative Examples 2-7, the microhardness of the weld area of ​​the β-titanium alloy joint is improved by single-step aging treatment or double-stage aging treatment, but not as good as the effect of the embodiment. Taking Example 2 as an example, in terms of tensile strength, the tensile strength of the β-titanium alloy joint prepared in Example 2 is as high as 1104.8MPa, which is 20.4% higher than the tensile strength of the β-titanium alloy joint prepared in Comparative Example 1, which is 917.4MPa. Compared with Comparative Examples 2-3 of single-step aging, the tensile strength of the β-titanium alloy joint prepared in Example 2 is increased by 9.1% and 23.1%, respectively. Compared with Comparative Examples 4-7 of multi-step aging, the tensile strength of the β-titanium alloy joint prepared in Example 2 is also significantly improved.

[0053] In addition, the β-titanium alloy joints prepared in Example 1, Comparative Example 1 and Comparative Example 2 were subjected to room temperature electrochemical corrosion performance tests. The electrolyte in the test process was 3.5% wt NaCl and the reference electrode was Ag / AgCl. The results showed that the corrosion current density of the β-titanium alloy joints prepared in Example 1, Comparative Example 1 and Comparative Example 2 was 0.05 μA / cm 2 , 0.09μA / cm 2 , 1.07μA / cm 2 , indicating that the β-titanium alloy joint prepared in the embodiment has the best corrosion resistance.

[0054] It can be seen from the above experimental results that the multi-step aging treatment method used in the embodiment of the present invention has a significant effect in improving the performance of the β titanium alloy joint.

[0055] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A heat treatment method for improving the performance of β titanium alloy joints, characterized in that: It includes: The β-titanium alloy joints were heat treated by a double-stage aging method of first low temperature and then high temperature.

2. The heat treatment method according to claim 1, characterized in that The double-stage aging method is: firstly, primary aging is performed at an aging temperature below the α phase transition temperature, and then secondary aging is performed at an aging temperature above the α phase transition temperature.

3. The heat treatment method according to claim 2, characterized in that: The β-titanium alloy joint is prepared by the following steps: two titanium alloy plates are connected by fusion welding or additive manufacturing, and then naturally cooled to room temperature by air cooling, wherein the thickness of the titanium alloy plate is 1-100 mm.

4. The heat treatment method according to claim 3, characterized in that: The weld center structure of the β titanium alloy joint is: a large number of coarse β columnar crystals + dispersed fine nano ω phases.

5. The heat treatment method according to claim 2, characterized in that: The temperature of the primary aging treatment is 200-400°C, the heating rate is 5-10°C / min, and the holding time is ≥5h.

6. The heat treatment method according to claim 5, characterized in that: After primary aging treatment, the central structure of the weld of the β-titanium alloy joint is: ellipsoidal ω phase + nano-needle-shaped α phase next to the ellipsoidal ω phase.

7. The heat treatment method according to claim 2, characterized in that: The temperature of the secondary aging treatment is 500-700°C, the heating rate is 1-5°C / min, and the holding time is 5-10h.

8. The heat treatment method according to claim 7, characterized in that: After secondary aging treatment, the central structure of the weld in the β-titanium alloy joint is: lath-like α phase.

9. A high-strength and high-hardness β-titanium alloy joint prepared by the heat treatment method according to any one of claims 1 to 8.

10. Application of the heat treatment method according to any one of claims 1 to 8 in post-weld joint weld treatment of β titanium alloy.